The Combination of City Branding and Ecocity: A Critical Review of Opportunities and Challenges in Indonesia - Sulistiowati, Rahayu; Yulianto; Meiliyana; Atika, Dewie Brima; Saputra, Dimas Adi (Research and Development Agency Ministry of Home Affairs, 2023)
This study aims to evaluate the combination of city branding and ecocity in Indonesia and critically examine the opportunities and challenges of developing both concepts. The background of this study was the increasing attention to the development of sustainable cities in Indonesia and the importance of city branding in enhancing a city's competitiveness. However, there is concern that city branding may overlook environmental sustainability aspects, which has led to the development of the ecocity concept as an alternative to improving the city's sustainability. The research method used in this study was a literature review. This literature review uses a systematic literature review approach with a narrative review method. The literature database used Google Scholar, CrossRef data, and Scopus data from 2010-2023. The results showed that developing a combination of City Branding and Ecocity has several opportunities and challenges that must be faced in Indonesia. The opportunities that arise are improving the positive image of cities in Indonesia, improving the quality of the environment in densely populated cities, and enhancing a city's competitiveness in investment and tourism. However, the challenges include limitations in resources, both financially and in terms of human resources, and obstacles in implementing sustainable policies and regulations. Nevertheless, Indonesia has significant opportunities to combine the concepts of City Branding and Ecocity.